Flow among higher education teachers - Habe, Katarina (Psihološka obzorja (Ljubljana), 2016)
The aim of the present study was to investigate job resources and demands and their relatedness to work flow. In line with the three-dimensional model of flow, absorption, work enjoyment and intrinsic work motivation were explored as separate outcomes. Our predictions were tested using a sample of 293 higher education teachers in Slovenia. The participants indicated their levels of flow, job demands (e.g., workload) and job resources (e.g., variety and autonomy) using the Slovenian version of the work flow inventory and job demands-resources scales. Our hypotheses were tested using moderated multiple regression where main as well as interactive effects between job resources and demands were examined. Autonomy and variety were found to enhance absorption, work enjoyment and intrinsic work motivation. Furthermore, autonomy was found to be the most important predictor of all the work flow dimensions. In contrast, workload was not significantly related to any of the outcomes. We also found interactive effec The aim of the present study was to investigate job resources and demands and their relatedness to work flow. In line with the three-dimensional model of flow, absorption, work enjoyment and intrinsic work motivation were explored as separate outcomes. Our predictions were tested using a sample of 293 higher education teachers in Slovenia. The participants indicated their levels of flow, job demands (e.g., workload) and job resources (e.g., variety and autonomy) using the Slovenian version of the work flow inventory and job demands-resources scales. Our hypotheses were tested using moderated multiple regression where main as well as interactive effects between job resources and demands were examined. Autonomy and variety were found to enhance absorption, work enjoyment and intrinsic work motivation. Furthermore, autonomy was found to be the most important predictor of all the work flow dimensions. In contrast, workload was not significantly related to any of the outcomes. We also found interactive effects of variety and workload as well as variety and autonomy on absorption.ts of variety and workload as well as variety and autonomy on absorption.
Keywords: flow; zanos; zadovoljstvo pri delu; job satisfaction; intrinsic motivation; visokošolski učitelji; job demands; notranja motivacija; job resources; delovne zahteve; delovni viri; higher education teachers